(untitled) (Journal of Current and Advance Medical Research, 2020)
Background: Women in different socio-demographic are presented with VIA positivity. Objective: The purpose of the present study was to see the socio-demographic characteristics and incidence of CIN of uterine cervix among of VIA positive women. Methodology: This cross sectional study was conducted in the Department Of Pathology at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh during the period of July 2007 to June 2008 for one (01) year. Patients who were colposcopically positive for cervical intraepithelial neoplasia and early invasive carcinoma or patients who are colposcopically negative but clinically suspicious for cervical neoplasia were included in this study. The clinical history was obtained by taking history with particular attention to age, age at marriage, parity, history of contraceptives, abnormal per vaginal discharge and post coital bleeding. The cervix was examined on naked eye by Cusco’s speculum to see whether it was healthy or not. Then it was examined by the colposcope after applying 3.0 to 5.0% acetic acid and colposcopic findings were collected. VIA positive cases were underwent colposcopy guided LEEP biopsy. Result: A total of 63 patients of different age group were recruited for this study. The mean with SD of age of this study population was 34.6±9.59 years. In this study, 41(65%) cases were diagnosed as cervical intraepithelial neoplasia (CIN). Incidence of CIN-I was 10 cases in age group 20 to 29 years. Most of the cases were in 30 to 39 (18 cases) years age group. Among 20 cases of high grade lesion (CIN-II/III) 9(45%) cases were in lower class, 8(40%) cases were in middle class and 3(15%) cases in upper class. Conclusion: In conclusion majority of the women were middle aged reproductive age group who are mostly in the lower class of socioeconomic class. Journal of Current and Advance Medical Research 2020;7(1): 7-11